The Influence of Health Service Quality, Perceived Value, and Perceived Price on Patient Loyalty and Patient Satisfaction - Weni Miftachul Jannah; Basuki Rachmat (Dinasti Publisher, 2025)
This study aims to analyze the influence of health service quality, perceived value, and perceived price on patient loyalty and satisfaction at the Benowo Community Health Center in Surabaya. The method used is a quantitative approach with explanatory research. Data were collected through a closed-ended questionnaire administered to 397 respondents and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0. The results of the study indicate that healthcare service quality, Perceived Value, and Perceived Price have a positive and significant influence on patient satisfaction and loyalty. These findings emphasize the importance of professional service, appropriate pricing, and perceived value in building loyalty toward public health services. This study suggests improving service quality based on empathy, price transparency, and leveraging digital technology as strategies to strengthen patient satisfaction and loyalty.